O Programa de Arrendamento Residencial - PAR: acesso diferenciado à moradia e à cidade - Bonates, Mariana Fialho (Universidade de São Paulo. Instituto de Arquitetura e Urbanismo, 2008)
This paper aims at analyzing the development of PAR (Programa de Arrendamento Residencial - Rental Housing Program) and its implications regarding the insertion of housing estates in urban space. Historically, Brazilian housing policy, especially during the BHN (1964-1986), promoted large-scale housing in land developments in the periphery of cities. After the closure of BNH, the production of large housing developments considerably declined. In 1999, when PAR war set up, the new, smaller in scale housing developments followed a different logic, having been located in the established, infra-structured neighborhoods already in place, thus occupying empty plots of land.